2016
DOI: 10.11152/mu-874
|View full text |Cite
|
Sign up to set email alerts
|

Intra-articular hyaluronic acid vs platelet-rich plasma in the treatment of hip osteoarthritis.

Abstract: viscosupplementation (hyaluronic acid [HA]) in hip osteoarthritis. Material and methods: A total of 43 patients affected by monolateral severe hip osteoarthritis (OA) were included in the study. Patients were randomized to receive either intra-articular PRP (3 ml) or HA (30 mg/2 ml; 1,000-2,900 kDa), 3 injections in total – 1/week. Clinical assessments for each patient were made at baseline (T0), 4 (T1), and 16 weeks (T2) of follow-up. The primary efficacy outcome was pain reduction as measured by VAS and by W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
90
0
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(93 citation statements)
references
References 30 publications
0
90
0
3
Order By: Relevance
“…However, we were not able to confirm the effect of other aspects of PRP on the treatment of KOA patients, including numbers of PRP injections (1 or ≥ 2), injection intervals (weekly or monthly), PRP spinning techniques (single or double), mean platelet concentration (> or < 5 × baseline), PRP category (LP-PRP or LR-PRP), and use an activator or not. In the past few years, more and more researchers noticed the potential of PRP in the treatment of musculoskeletal diseases, such as rotator cuff tear, lateral epicondylitis, patellar tendinopathy, osteoarthritis, and Achilles tendon repair [19][20][21][22][23][24][25][26]. Given the properties of regenerative effect and anti-inflammatory potential in PRP, a number of researches [19,23,24,[27][28][29][30][31][32][33][34][35] explored the curative effect of intraarticular PRP injection in the treatment of patients with osteoarthritis, especially with knee osteoarthritis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, we were not able to confirm the effect of other aspects of PRP on the treatment of KOA patients, including numbers of PRP injections (1 or ≥ 2), injection intervals (weekly or monthly), PRP spinning techniques (single or double), mean platelet concentration (> or < 5 × baseline), PRP category (LP-PRP or LR-PRP), and use an activator or not. In the past few years, more and more researchers noticed the potential of PRP in the treatment of musculoskeletal diseases, such as rotator cuff tear, lateral epicondylitis, patellar tendinopathy, osteoarthritis, and Achilles tendon repair [19][20][21][22][23][24][25][26]. Given the properties of regenerative effect and anti-inflammatory potential in PRP, a number of researches [19,23,24,[27][28][29][30][31][32][33][34][35] explored the curative effect of intraarticular PRP injection in the treatment of patients with osteoarthritis, especially with knee osteoarthritis.…”
Section: Discussionmentioning
confidence: 99%
“…Various growth factors and cytokines are released after the degranulation of platelets and to accelerate cartilage matrix synthesis, restrain synovial membrane inflammation, and promote cartilage healing [17,18]. Owing to the properties of regenerative effect and anti-inflammatory potential, PRP is widely used in musculoskeletal diseases, such as rotator cuff tear, lateral epicondylitis, patellar tendinopathy, osteoarthritis [19][20][21][22][23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%
“…Battaglia et al [55] found improved function and decreased pain but LP‐PRP was not found superior to HA at 1‐year follow‐up. Di Sante et al [56] reported superior short‐term pain relief with hip intra‐articular PRP injection; however, long‐term pain relief was superior with HA injection. A 2018 meta‐analysis of randomized controlled trials of PRP vs HA in hip OA [57] concluded that PRP‐treated patients demonstrated significant decrease of pain at 2 months with equivalent improvement of function and no significant difference noted at 6 and 12 months.…”
Section: Common Regenerative Methodsmentioning
confidence: 99%
“…Published data are mixed with fewer robust studies for Achilles and patella tendinopathy, limiting our ability to draw conclusions about efficacy. Table 2 presents a list of studies [49‐89] and levels of evidence.…”
Section: Common Regenerative Methodsmentioning
confidence: 99%
“…Так, в работе L. Di Sante и соавт. [75] оценивалась эффективность ОТП при лечении ОА тазобедренного сус-тава. 43 пациента получили по три еженедельных внутри-суставных инъекции ОТП или ГРК.…”
Section: обогащенная тромбоцитами плазмаunclassified